Cardiovascular Autonomic Neuropathy Predicts Higher HbA1c Variability in Subjects with Type 2 Diabetes Mellitus - Yang, Yeoree; Lee, Eun-Young; Cho, Jae-Hyoung; Park, Yong-Moon; Ko, Seung-Hyun; Yoon, Kun-Ho; Kang, Moo-Il; Cha, Bong-Yun; Lee, Seung-Hwan (Diabetes & metabolism journal, 2018)
Background This study aimed to investigate the association between the presence and severity of cardiovascular autonomic neuropathy (CAN) and development of long-term glucose fluctuation in subjects with type 2 diabetes mellitus.Methods In this retrospective cohort study, subjects with type 2 diabetes mellitus who received cardiovascular autonomic reflex tests (CARTs) at baseline and at least 4-year of follow-up with ≥6 measures of glycosylated hemoglobin (HbA1c) were included. The severity of CAN was categorized as normal, early, or severe CAN according to the CARTs score. HbA1c variability was measured as the standard deviation (SD), coefficient of variation, and adjusted SD of serial HbA1c measurements.Results A total of 681 subjects were analyzed (294 normal, 318 early, and 69 severe CAN). The HbA1c variability index values showed a positive relationship with the severity of CAN. Multivariable logistic regression analysis showed that CAN was significantly associated with the risk of developing higher HbA1c variability (SD) after adjusting for age, sex, body mass index, diabetes duration, mean HbA1c, heart rate, glomerular filtration rate, diabetic retinopathy, coronary artery disease, insulin use, and anti-hypertensive medication (early CAN: odds ratio [OR], 1.65; 95% confidence interval [CI], 1.12 to 2.43) (severe CAN: OR, 2.86; 95% CI, 1.47 to 5.56). This association was more prominent in subjects who had a longer duration of diabetes (>10 years) and lower mean HbA1c (<7%).Conclusion CAN is an independent risk factor for future higher HbA1c variability in subjects with type 2 diabetes mellitus. Tailored therapy for stabilizing glucose fluctuation should be emphasized in subjects with CAN.